Effects of hydrogen irradiation on the optical and electronic properties of site‐controlled InGaAsN V‐groove quantum wires. Issue 4 (22nd January 2013) - Felici, Marco; Polimeni, Antonio; Lavenuta, Giovanna; Tartaglini, Elena; De Luca, Marta; Capizzi, Mario; Notargiacomo, Andrea; Carron, Romain; Fekete, Dan; Gallo, Pascal; Dwir, Benjamin; Rudra, Alok; et al.
Abstract The properties of InGaAsN V‐groove QWRs are assessed here by polarization‐dependent photoluminescence (PL) and micro‐magneto‐PL. Both the polarization anisotropy of the QWR emission and the strong dependence of the diamagnetic shift on the orientation of the applied magnetic field confirm the 1D nature of the QWR excitons. Further, the possibility of passivating N impurities by H irradiation is used to estimate the N content (x) in the QWRs by turning off the effects of N incorporation. Both the H‐induced blueshift of the QWR emission (70 meV) and the measured value of the electron effective mass are consistent with x ∼1%. Nitrogen is also found to enhance the In intake in the QWR, likely due to the strain reduction resulting from the smaller lattice parameter of the InGaAsN alloy. Such strain reduction is also responsible for the quick decay of the degree of linear polarization (ρ) of the QWR emission with increasing temperature, indicating a small splitting between the QWR valence‐band levels. In fully hydrogenated samples, conversely, ρ remains roughly constant up to ∼240 K, suggesting the recovery of a larger energy separation between the QWR hole states upon N passivation. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)